2013
DOI: 10.1007/s10147-013-0606-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hsp90 and 70 sensitizes melanoma cells to hyperthermia using ferromagnetic particles with a low Curie temperature

Abstract: Combining Hsp90/70 inhibition with hyperthermia appears to increase their antitumor effects. Thus, the combination of FMP-mediated, self-regulating hyperthermia with Hsp90/70 inhibition has important implications for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
7
28
0
Order By: Relevance
“…Studies have confirmed that heat-induced HSP90 expression protects cells by preventing protein degradation, and thus leads to thermoresistance. 23,24 Although cancer stem cells show poor response to radiotherapy and chemotherapy, thermotherapy can effectively eliminate cancer stem cell and inhibit their stem cell-like properties. 13 In this study, inhibiting the thermoresistance of CD90 + LCSCs markedly enhanced the thermal-induced apoptosis.…”
mentioning
confidence: 99%
“…Studies have confirmed that heat-induced HSP90 expression protects cells by preventing protein degradation, and thus leads to thermoresistance. 23,24 Although cancer stem cells show poor response to radiotherapy and chemotherapy, thermotherapy can effectively eliminate cancer stem cell and inhibit their stem cell-like properties. 13 In this study, inhibiting the thermoresistance of CD90 + LCSCs markedly enhanced the thermal-induced apoptosis.…”
mentioning
confidence: 99%
“…We previously developed a thermo‐sensitive ferromagnetic implant with low Curie temperature (FILCT) with a particle diameter of 50–150 μm and a Curie point of 43 °C, which is a suitable temperature for treatment . Next, we confirmed that this approach enhanced the antitumor effect and improved the survival rate when combined with a heat shock protein 90 inhibitor in a rat melanoma model . However, because of the low heating efficiency of the FILCT, it was difficult to heat up to 43 °C when treating a human body.…”
Section: Introductionmentioning
confidence: 75%
“…58 An important mediator of the cell stress response is heat shock protein 90 (Hsp90), which has been reported to be upregulated in melanoma, 59 and its inhibition, along with the inhibition of Hsp70, has been reported to enhance the sensitivity of melanoma cells to the anti-tumor effects of hyperthermia. 60 Interestingly, there is evidence showing that curcumin synergistically enhances the anti-tumor effect of bortezomib in melanoma through inhibition of Hsp90 expression. 61 Hemeoxygenase/biliverdin reductase (HO/BVR) is another main component of the cell stress response.…”
Section: Curcumin As a Therapeutic Agent In Melanomamentioning
confidence: 99%